Preparation and characterization of epoxidized-30% poly (methyl methacrylate)-grafted natural rubber polymer electrolytes for electrochemical double layer supercapacitor / Khuzaimah Nazir - Nazir, Khuzaimah (Institute of Graduate Studies, UiTM, 2018)
This dissertation focuses on the preparation and characterization of epoxidized- 30% poly(methyl methacrylate) grafted natural rubber (EMG30)-salt complexes and plasticized EMG30-salt complexes. In the present study, EMG30 as polymer host, lithium trifluoromethanesulfonate (LiCF3S03) as doping salt and ethylene carbonate (EC) as a plasticizer were used in the preparation of solid polymer electrolytes (SPEs) and gel polymer electrolytes (GPEs). The EMG30 was prepared by performic epoxidation method with various time reaction. Proton nuclear magnetic resonance (1HNMR) and Fourier transform infrared spectroscopy (FTIR) spectra confirm a new peak at 2.70-2.71 ppm and 871 cm-1 which were assigned to the epoxy group. 54.6, 62.3 and 50.0 mol% of epoxidation content were obtained in EMG30 at 6, 9 and 12 hours of time reactions, respectively. SPEs and GPEs based on EMG30 were prepared by the solution cast technique with different weight percent (wt.%) of LiCF3S03 and EC. FTIR spectroscopy studies have shown that coordination of Li+ ions has occurred on the oxygen (O) atom in the carbonyl (C=0) group, ether group (0-CH3) and epoxy (C-O-C) group of EMG30. X-ray diffraction (XRD) analysis confirmed amorphous nature of EMG30 samples. Thermogravimetric analysis (TGA) have shown that thermal stability of EMG30 is increased compared to pure MG30. The differential scanning calorimetry (DSC) analysis found the epoxidation reaction has increased the Tg value of EMG30 (Tg ~ - 39.1 °C) due to the restriction of hydrogen bonding…